Editor's Choice – Incidence of Stroke Following Thoracic Endovascular Aortic Repair for Descending Aortic Aneurysm: A Systematic Review of the Literature with Meta-analysis. (February 2017) - von Allmen, R.S.; Gahl, B.; Powell, J.T.
Abstract : Objective: Stroke is an increasingly recognised complication following thoracic endovascular aortic repair (TEVAR). The aim of this study was to systematically synthesise the published data on perioperative stroke incidence during TEVAR for patients with descending thoracic aneurysmal disease and to assess the impact of left subclavian artery (LSA) coverage on stroke incidence. Methods: A systematic review of English and German articles on perioperative (in-hospital or 30 day) stroke incidence following TEVAR for descending aortic aneurysm was performed, including studies with ≥50 cases, using MEDLINE and EMBASE (2005–2015). The pooled prevalence of perioperative stroke with 95% CI was estimated using random effect analysis. Heterogeneity was examined using I 2 statistic. Results: Of 215 studies identified, 10 were considered suitable for inclusion. The included studies enrolled a total of 2594 persons (61% male) between 1997 and 2014 with a mean weighted age of 71.8 (95% CI 71.1–73.6) years. The pooled prevalence for stroke was 4.1% (95% CI 2.9–5.5) with moderate heterogeneity between studies ( I 2 = 49.8%, p = .04). Five studies reported stroke incidences stratified by the management of the LSA, that is uncovered versus covered and revascularised versus covered and not-revascularised. In cases where the LSA remained uncovered, the pooled stroke incidence was 3.2% (95% CI 1.0–6.5). There was, however, an indication that stroke incidence increased following LSA coverage, to 5.3% (95% CI 2.6–8.6) in those with a revascularisation and 8.0% (95% CI 4.1–12.9) in those without revascularisation. Conclusion: Stroke incidence is an important morbidity after TEVAR, and probably increases if the LSA is covered during the procedure, particularly in those without revascularisation.